2017
DOI: 10.18203/2394-6040.ijcmph20172169
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of family burden and quality of life between caregivers of schizophrenia and dementia patients

Abstract: Background: In chronic mental diseases, as the disease progresses, it carries with tremendous burden both physically and psychologically on the family members, who are usually in the process of caregiving. The quality of life (QOL) of these caregivers is directly related to the subjective and objective burden of the illness. The objective of the study was to assess and compare the level of family burden and QOL between caregivers of Schizophrenia and Dementia patients as well as to find out the relationship be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 14 publications
2
4
0
Order By: Relevance
“…The IEQ results derived from this real-world survey indeed show that caring for patients with schizophrenia or bipolar disorder with agitation has a significant impact on caregiver life. In agreement with previous studies using alternative methodologies, caregivers are affected across multiple domains [ 28 , 29 ]. The values are comparable to previously reported IEQ scores in bipolar disorder, [ 22 ] and schizophrenia, [ 23 ] with the differences observed most likely attributable to the differences in populations with neither study assessing agitation as a specific subset of symptoms.…”
Section: Discussionsupporting
confidence: 91%
“…The IEQ results derived from this real-world survey indeed show that caring for patients with schizophrenia or bipolar disorder with agitation has a significant impact on caregiver life. In agreement with previous studies using alternative methodologies, caregivers are affected across multiple domains [ 28 , 29 ]. The values are comparable to previously reported IEQ scores in bipolar disorder, [ 22 ] and schizophrenia, [ 23 ] with the differences observed most likely attributable to the differences in populations with neither study assessing agitation as a specific subset of symptoms.…”
Section: Discussionsupporting
confidence: 91%
“…(Lasebikan and Ayinde, 2013;Swain et al, 2017). This result is in line with the findings of Chen's survey in Beijing, where approximately 70% of respondents reported experiencing mental stress burden(Chen et al, 2019).…”
supporting
confidence: 87%
“…Similarly, Ponangi et al, (2014) has found that burden of care was high in both subjective and objective scales and factors like female sex, middle age and severity of illness had effect on extent of burden. Swain et al, (2017) shows the level of subjective perception of the care givers towards their responsibilities. While half of the care givers of dementia patients felt that the family burden was little, nearly three quarters (73.4%) of those caring for schizophrenia patients had similar perception.…”
Section: Discussion On Comparison Of Family Burden Of Caregivers Of T...mentioning
confidence: 99%
“…All the items of this scale are rated on 3point scale (viz, severe burden, Moderate burden and No burden). Similar tool was used by Swain et al, (2017), Yazici et al, (2016) and Geriani et al, (2015 to examine the family burden among the caregivers of persons with schizophrenia.…”
Section: Dimensionsmentioning
confidence: 99%